Reexamining the factorial validity of the 16-item scale measuring need for cognition - Zhang, Ying; Klopp, Eric; Dietrich, Heike; Brünken, Roland; Krause, Ulrike-Marie; Spinath, Birgit; Stark, Robin; Spinath, Frank M. (European journal of psychological assessment, 2020)
A growing body of studies has emphasized the need to consider method effects due to positively and negatively worded items for a better understanding of the factorial structure of psychological constructs. In particular, several researchers identified such method factors besides the content factor for various scales measuring Need for Cognition (NFC). However, regarding the factorial validity of the 16-item NFC scale developed by Bless, Wänke, Bohner, Fellhauer, and Schwartz (1994), only a one-factor structure without the inclusion of possible method factors has been examined so far. Therefore, we considered such method factors in a broader reexamination of the factorial validity of this measure by investigating a range of structural models in two samples (n = 830, n = 500). We found that a one-factor solution as proposed by Bertrams and Dickhäuser (2010) and Bless et al. (1994) did not fit the data, whereas the inclusion of method factors improved the model fit significantly. According to our results, the model including both the content factor and two uncorrelated method factors yielded the best model fit. In sum, our results provide an extended view of the factorial validity of the 16-item scale of NFC.
Published online: September 18, 2018
Gesehen am 23.04.2020